Autonomous spacecraft rendezvous with finite time convergence. Issue 11 (November 2015) - He, Shaoming; Lin, Defu; Wang, Jiang
Abstract: This paper considers the application of nonsingular terminal sliding mode (NTSM) control and extended state observer (ESO) to the circular orbital autonomous spacecraft rendezvous problem subject to model uncertainties and external disturbances. With the aid of Lyapunov stability criteria, we first develop a continuous NTSM-based robust control law and its finite-time convergence characteristic is proven in theory. As the upper bound of the lumped uncertainty cannot be obtained in practice, an ESO based composite ESO–NTSM controller is then presented to achieve high tracking accuracy even under actuator/thruster failures and input saturations. Simulation results of a final closing rendezvous example are provided to demonstrate the effectiveness of the proposed composite ESO–NTSM guidance approach.